Automated simulation setup in HFSS for on-chip transformer - Tan, Bennett Chin Hin. (2010)
This report aims to provide a comprehensive review of the Final Year Project, Automated Simulation Setup in High Frequency Structure Simulator (HFSS) for On-Chip Transformer, which pertains to the investigation and design of silicon-based spiral on-chip inductor. Monolithic integrated lumped planar transformers have several advantages when using them in power amplifiers, mixers, oscillators and other radio frequency circuits. The metallization of a semiconductor process defines the possibilities for transformer design. The background of on-chip transformers, with respect to the requirements of the project, is being presented in the literature review. This includes the different layouts of the transformer, the metallization structure and a few examples on the layouts that have already been developed. In this project, to construct the automated setup, Ansoft’s High Frequency Structure Simulator is being used extensively. Since the transformer is essentially a magnetic coupled pair of inductors and the structure of inductors is much simpler, the calibration of HFSS is started with inductors. A brief background on transformers and inductors, the designing process and the challenges faced are also presented